Upaya Pencegahan Peredaran Narkotika Oleh Tim P4gn (Pencegahan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkoba)Kabupaten Sukoharjo Pada Anak Usia Sekolah - Putro, Hisyam Mega; , Dr. Natangsa Surbakti, S. H., M. Hum; , Bambang Sukoco S.H.,M.H (2016)
Narcotics is a substance if abused will cause harmful effects to health, so P4GN trying to prevent drug trafficking. For the purpose of this study describes a precaution and Sukoharjo P4GN efforts against narcotics trafficking involving children. The research approach used to conduct this study was Juridical sociological research methods. Methods of data analysis using a qualitative approach. The results showed. The work program run by P4GN Sukoharjo form of outreach programs, drug prevention promotion business. Activities aimed at children's special about the field of prevention in the form of socialization to schools in the form of counseling dangers of drugs. P4GN Rehabilitasion activity to the consultation is more personal problems and the hypnoteraphy / suggestion in order to stay away from drugs, then a coaching program of street children in the form of street children schools and vocational training street children.